Salacia campestris root bark extract: peroxidase inhibition, antioxidant and antiradical profile - Rebuglio Vellosa, Jose Carlos; Khalil, Najeh Maissar; Gutierres, Vainia Ortega [UNESP]; Santos, Vainia Aparecida de Freitas Formenton Macedo dos [UNESP]; Furlan, Maysa [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Oliveira, Olga Maria Mascarenhas de Faria [UNESP] (Universidade de São Paulo (USP), Conjunto Quimicas, 2009)
Reactive oxygen species (ROS) and free radical species have been implicated in initiating or accompanying many diseases in living organisms; there is thus, a continual need for antioxidants molecules to inactivate ROS/free radicals. Many studies of plants crude extracts have demonstrated free-radical scavenging and antioxidant action. Salacia species have long been used, in several countries, as traditional medicines against certain diseases and for their anti-inflammatory properties. In this Study, Salacia campestris Walp (Hippocrateaceae) root bark ethanol extract (ScEtOH) was assessed for its ability to scavenge free radicals and reactive oxygen species; the results were expressed as percentage inhibition of the active species. ScEtOH was efficient against studied species: DPPH radical (obtained inhibition = 30%), ABTS(center dot+) (IC(50) = 1.8 +/- 0.8 mu g/mL), HOCI (IC(50) = 1.7 +/- 0.1 mu g/mL), O2(center dot-) (obtained inhibition = 32%), and NO(center dot) (obtained inhibition = 18%). Peroxidase activity inhibition was evaluated through the guaiacol oxidation reaction catalyzed by hemin, HRP and. myeloperoxidase (MPO); data showed that ScEtOH at 10 mu g/mL led to 54 and 51% of inhibition, respectively, for the hemin and HRP systems. In the MPO system, ScEtOH promoted a 50% inhibition at 8.9 mu g/mL, whereas quercetin, a powerful MPO inhibitor, inhibited this system at 1.35 mu g/mL.